(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research aims to (1) find out how teachers conduct distance learning during the COVID-19 pandemi in Mathematics; and (2) find out whether the teacher has optimally used all the features in the LMS in Mathematics in the Meeting of Teachers of Mathematics in Klaten Regency. This type of research is descriptive qualitative research. The subjects in the study were 26 teachers in the Mathematics Meeting of Teachers of Mathematics in Klaten Regency. The data analysis used in this research are (1) inductive theory; and (2) data analysis by Miles and Huberman, namely data reduction, data presentation, conclusion drawing and leveraging. Through the questionnaire submitted, it can be said that the use of various learning management systems according to the needs and circumstances of each school and the lack of technological knowledge skills make the use of LMS features less than optimal so that learning objectives cannot be achieved optimally.